The potential growth impact of fiscal consolidations - Haryo Kuncoro (Universitas Islam Indonesia, 2021)
Purpose - This paper aims at analyzing the feasibility of fiscal consolidation implementation in the case of Indonesia. The main question to be investigated is whether fiscal consolidation will deteriorate economic growth or not.Methods - This research uses various probabilistic models to assess the successfulness of fiscal adjustments. Probit and logit models are used as a preliminary estimate. The robustness checks are conducted by binary extreme value and Tobit models.Findings - The results indicate that the magnitude of government revenue is less than that of government spending. They seem that increasing government revenue (taxes, for instance) is less harmful compared to reducing expenditures, which denies empirically what Keynesian economists approve of.Implication - The results highlight that Indonesia’s fiscal authority should immediately reform the economic, regulatory, and institutional environments in adopting fiscal austerity policies. The reforms are strongly required to realize fiscal health as well as to promote economic growth.Originality - This paper contributes the literature on fiscal policy in developing countries. Unlike other empirical studies, this research compares the actual output over the potential output, instead of the past actual output, to evaluate the successfulness of fiscal consolidations.